Identity Crisis In The Modern Era: A Qur’anic Perspective Based On Ibn Qayyim Al-Jauziyyah’s Tafsir - Elit Ave Hidayatullah; Aliefia Salsabila Puteri Rintani; Nayl Syakil Bilqist (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2026)
Identity crisis has become a significant challenge for adolescents in the modern era, particularly due to social pressures, digital culture, and globalization, which lead to confusion in self-concept and lower self-esteem. This paper positions itself within the Islamic perspective of tazkiyatun nafs according to Ibn Qayyim al-Jauziyyah, aiming to analyze how spiritual purification can address identity crises among contemporary youth. Using a literature review methodology, this study examines classical tafsir, Islamic spiritual texts, and modern psychological research related to adolescent identity formation. The discussion highlights the three stages of tazkiyatun nafs: takhalli, the purification of the soul from negative traits and harmful influences, tahalli, the cultivation of virtuous character and spiritual awareness, and tajalli, the manifestation of divine values in personal and social life. Findings indicate that integrating these stages enables adolescents to develop authentic, dignified identities, fostering both psychological and spiritual well-being. The study demonstrates that Islamic spiritual practices offer a holistic approach to navigating identity challenges in the digital and globalized era.